Effect of functionalization on electrospun PVDF nanohybrid for piezoelectric energy harvesting applications - Tiwari S.; Dubey D.K.; Prakash O.; Das S.; Maiti P. (My University, 2025)
Carbon nanofibers (CNF) have gained much attention in the field of energy and preparation of nanofibers with polymer, a recent method to increase its mode of applications. Functionalization of CNF has been done to enhance its surface property for better dispersion and interaction with polymer matrix and ultimately applied for energy harvesting applications. Electrospun composite fibers prepared through the electrospinning process shows better morphological, structural and thermal properties on incorporation of the electroactive filler to the pristine poly(vinylidene fluoride) (PVDF). Functionalization of the filler leads to thinning of the fiber with significantly enhanced piezo phase generation as compared to the neat PVDF. The rise in piezo-active phases (85% for PVDF-functionalized CNF hybrid) is clearly demonstrated from the structural and thermal techniques which confirm the materials potential as efficient piezoelectrics. The role of the structural conformations and the effect of the filler are analysed using the computational studies. The change in properties of the material in presence of electric field and electroactive filler is well demonstrated using the theoretical analysis. The device developed from the electrospun scaffold produces maximum (peak-to-peak) output voltage of 44 V, maximum current of 1.3 μA and power of 57.2 μW through finger tapping mode which is considerably higher as compared to the pristine PVDF scaffold. The device can produce good output from other modes like bending, pinning and foot tapping which may be due to the mechanistic pathway of the charge generation due to the external pressure which leads to high transformation of the non-piezo part to piezo-active part that increases the efficiency of the device. © 2023 Elsevier Ltd